Not all about farming: Understanding aspirations can challenge assumptions about rural development - Mausch, Kai; Harris, Dave; Dilley, Luke; Crossland, Mary; Pagella, Tim; Yim, Jules; Jones, Emma (Springer, 2021)
Rural development is a political topic in which debate has been more focussed on externally identified needs than on demands or aspirations of the rural population and polarised between the attractions of urban income earning opportunities and the importance of rural farming communities for national food provision. The heterogeneity of local aspirations and their implications for development have barely been considered. We explore the aspirations of residents of three contrasting regions in Kenya that vary in their agricultural and off-farm potential. We argue that opportunities are a major framing influence on aspirations but there is important, and routinely overlooked, diversity within the communities which could inform future options for effective development. We outline how development initiatives could be redesigned to align more closely with aspirations. However, aspirations are a complex concept and, while our approach offered novel insights, these would be enriched when combined with household survey data.